2020
DOI: 10.1111/famp.12585
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed‐method Study of Individual, Couple, and Parental Functioning During the State‐regulated COVID‐19 Lockdown in Spain

Abstract: During the recent COVID‐19 outbreak in Spain, we explored the individual and relational well‐being of people confined together with their partners and/or children during the first 3 weeks of state‐regulated lockdown. Adults 18 years or older (N = 407) completed an online survey that included demographic, household, and employment information along with standardized measures of psychological distress (State‐Trait Anxiety and Beck Depression) and relationship functioning—either the Dyadic Adjustment Scale if the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
188
2
14

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(225 citation statements)
references
References 34 publications
(49 reference statements)
21
188
2
14
Order By: Relevance
“…These results highlight how COVID-19 concerns significantly threaten individuals’ psychological well-being, in terms of energy, mental health, and social functioning, confirming our first hypothesis (H1). The COVID-19 situation may have induced intense feelings of concern, due to the seriousness of the health emergency, the consequent economic crisis, job instability, and uncertainty about the future ( Ferrucci et al, 2020 ; Mazza et al, 2020 ; Pagnini et al, 2020 ; Rossi et al, 2020 ), also in couples ( Günther-Bel et al, 2020 ; Panzeri et al, 2020 ; Rapelli et al, 2020 ). These concerns, likely amplified by stressors related to the virus containment measures (e.g., prolonged co-habitation, lack of formal and informal support networks, etc.…”
Section: Discussionmentioning
confidence: 99%
“…These results highlight how COVID-19 concerns significantly threaten individuals’ psychological well-being, in terms of energy, mental health, and social functioning, confirming our first hypothesis (H1). The COVID-19 situation may have induced intense feelings of concern, due to the seriousness of the health emergency, the consequent economic crisis, job instability, and uncertainty about the future ( Ferrucci et al, 2020 ; Mazza et al, 2020 ; Pagnini et al, 2020 ; Rossi et al, 2020 ), also in couples ( Günther-Bel et al, 2020 ; Panzeri et al, 2020 ; Rapelli et al, 2020 ). These concerns, likely amplified by stressors related to the virus containment measures (e.g., prolonged co-habitation, lack of formal and informal support networks, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Although these aspects can be disrupted in situations of distress, they may also serve as resilience factors. Indeed, positive interactions among family members, supportive relationships, and cohesion have been found to be conducive to less parenting stress and better family quality of life in the context of disasters (Günther-Bel, Vilaregut, Carratala, Torras-Garat, & Pérez-Testor, 2020 ; McDermott & Cobham, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, family well-being is influenced by many factors, some external such as social disruption by COVID-19 measures but also altered couple relationships changed due to home-office and home-schooling. Data show that in previous pandemics the couple relationships in families can also improve in some cases as both partners were able to support each other [ 9 , 14 , 15 ]. A recent study from China has already shown that parents of children hospitalized due to the pandemic had more serious mental health problems than parents of children hospitalized due to medical issues unassociated with the pandemic [ 16 ].…”
Section: Introductionmentioning
confidence: 99%